Use of Hooke's law for stabilizing future smart grid the electric spring concept - Lee,CK; Tan,SC; Wu,FF; Hui,SYR; Chaudhuri,B (2013 IEEE Energy Conversion Congress and Exposition Ecce 2013, 2013)
Hooke's law for mechanical springs was developed in the 17th century. Recently, new power electronics devices named electric springs have been developed for providing voltage regulation for distribution networks and allowing the load demand to follow power generation. This paper summarizes recent R&D on electric springs and their potential functions for future smart grid. Electric springs can be associated with electric appliances, forming a new generation of smart loads which can adapt according to the availability of power from renewable energy sources. When massively distributed over the power grid, they could provide highly distributed and robust support for the smart grid, similar to the arrays of mechanical springs supporting a mattress. Thus, the 3-century old Hooke's law in fact provides a powerful solution to solving some key Smart Grid problems in the 21st Century. © 2013 IEEE.